ON THE PRODUCTION BY SOLAR PROTONS OF 126XE VIA TE (P,XN) REACTIONS - Begemann F.; Mathew K.J. (My University, 1996)
Results are reported for cumulative thick-target yields of 126,128,130Xe upon irradiating metallic tellurium of natural isotopic composition with protons of ~3.7 MeV, 10 MeV, 14 MeV, and 17 MeV, respectively. Combined with existing data we find, for a spectrum of solar protons as derived from lunar studies (Ro = 100 MV), a spectrum-averaged yield η (126Xe)Te = 4.2 x 10-4126 Xe atoms per incident proton and yield ratios η (128Xe)/η (126Xe) = 1.42 and η (130Xe)/η (126Xe) = 0.33. In order to account for the excesses of 126Xe occasionally observed, up to 3.0 x 10-11 cm3 STP/g in bulk lunar samples and 250 times smaller ones in stone meteorites, the product of tellurium concentration, in ppm, times the proton dose must have been 2 x 1018 cm-2 and 8 x 1015 cm-2, respectively. If the irradiated matter was a surface layer of a regolith, the 126Xe thus produced will be diluted, by mixing with deeper layers, to an extent that depends on time of exposure and rate of ''gardening.'' It remains to be shown, by analysing suitable samples for both xenon and tellurium, whether this production mode can quantitatively account for the excesses of 126Xe that are occasionally observed in lunar samples and gas-rich meteorites.